Interpretive research design : concepts and processes - Schwartz-Shea, Peregrine , 1955-; Yanow, Dvora (Routledge series on interpretive methods, 2012)
"Research design is fundamentally central to all scientific endeavors, at all levels and in all institutional settings. This book is a practical, short, simple, and authoritative examination of the concepts and issues in interpretive research design, looking across this approach's methods of generating and analyzing data. It is meant to set the stage for the more "how-to" volumes that will come later in the Routledge Series on Interpretive Methods, which will look at specific methods and the designs that they require. It will, however, engage some very practical issues, such as ethical considerations and the structure of research proposals. Interpretive research design requires a high degree of flexibility, where the researcher is more likely to think of "hunches" to follow than formal hypotheses to test. Yanow and Schwartz-Shea address what research design is and why it is important, what interpretive research is and how it differs from quantitative and qualitative research in the positivist traditions, how to design interpretive research, and the sections of a research proposal and report"--Provided by publisher.